Characteristics of Command and Control in Response to Emergencies and Disasters - Trnka, J.; Woltjer, R. (Assessing Command and Control Effectiveness, 2014)
Controllers are a part of larger control systems that influence what and how specific response operations are managed and related command and control work performed. Controllers in emergency and disaster response operations need to be adaptive in multiple dimensions in order to accomplish their goals. The three main dimensions of adaptation are: resource-driven adaptation, control-driven adaptation and adaptation to unexpected disturbances and changes. The chapter describes and discusses the main characteristics of response operations and the related command and control work. First, emergencies and disasters are distinctive phenomena that require specific management of response operations. Secondly, management of this type of response operation is a dynamic control process controlled by controllers. Thirdly, controllers need to be adaptive in multiple dimensions due to the nature of response operation. The adaptation may also concern use of diverse organizational and temporal configurations of command and control work over time.